2018
DOI: 10.5006/2893
|View full text |Cite
|
Sign up to set email alerts
|

Corrosion and Hydrogen Permeation in H2S Environments with O2 Contamination, 1: Tests on Pure Iron at High H2S Concentration

Abstract: Materials selection in the oil and gas industry relies on engineering standards, such as NACE TM0177 and NACE TM0284, which stipulate that oxygen pollution should be avoided during materials testing in H 2 S-containing media. In this paper, we explore the manner in which traces of oxygen can modify the test solution chemistry and the corrosion of/ hydrogen permeation across iron membranes in H 2 S-containing solutions. Oxygen pollution is shown to strongly influence solution chemistry, through the introduction… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(14 citation statements)
references
References 17 publications
(24 reference statements)
1
13
0
Order By: Relevance
“…The validity of its usage in such experiments is outlined in Part 1. 5 For the studied conditions, it is observed that average permeation currents diminish with decreasing P H 2 S (i.e., lower [H 2 S] aq and [H + ] aq ). Quite remarkably, and as already observed in the previous article, permeation efficiencies are close to 100% for all tests without O 2 contamination, albeit more scattering appears at 0.1 kPa H 2 S. For this test condition (0.1 kPa H 2 S without O 2 ), it is believed that corrosion current densities were overestimated, due to insufficient influence of the charge transfer resistance in the frequency range of impedance measurements (Figure 4[g]).…”
Section: Electrochemical Studymentioning
confidence: 80%
See 3 more Smart Citations
“…The validity of its usage in such experiments is outlined in Part 1. 5 For the studied conditions, it is observed that average permeation currents diminish with decreasing P H 2 S (i.e., lower [H 2 S] aq and [H + ] aq ). Quite remarkably, and as already observed in the previous article, permeation efficiencies are close to 100% for all tests without O 2 contamination, albeit more scattering appears at 0.1 kPa H 2 S. For this test condition (0.1 kPa H 2 S without O 2 ), it is believed that corrosion current densities were overestimated, due to insufficient influence of the charge transfer resistance in the frequency range of impedance measurements (Figure 4[g]).…”
Section: Electrochemical Studymentioning
confidence: 80%
“…The relevant preparation and experimental procedures are detailed in Part 1. 5 Pure H 2 S (>99.5% H 2 S) and H 2 S/N 2 gas cylinders (10% H 2 S/balance N 2 ), (1% H 2 S/balance N 2 ), and (0.1% H 2 S/balance N 2 ) were used to establish the different partial pressures of 10 kPa, 1 kPa, and 0.1 kPa, respectively, in the tests. The partial pressure of water vapor at 24°C being 3 kPa, a strict calculation of H 2 S partial pressures leads to a 4% decrease in the reported values.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…With regards the test gas, either pure H 2 S (> 99.5% H 2 S), or a pure H 2 S + O 2 mixture (using a separate O 2 gas line to mix in an appropriate amount to provide a dissolved oxygen concentration [O 2 ] aq of 300 parts per billion (ppb or µg/L) by weight) were used to represent 'O 2 -free' and 'O 2 -polluted' testing scenarios respectively. 7 All tests were conducted at atmospheric pressure at a temperature of T = 24°C for a period of 720 h.…”
Section: Table 1: Acetate Concentration Used In Test Solutions (T = 24°c P H2s ~100 Kpa)mentioning
confidence: 99%